1997
DOI: 10.3109/10826089709055878
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Sports Participation in Adolescents: A Cross-Sectional Survey among High School Students in Italy

Abstract: All the male students in a high school in Brescia, North Italy (about 195,000 inhabitants) in Grades 9 through 13 were given a self-administered anonymous questionnaire during school time. Among the 1,462 students who filled in a valid questionnaire, 29.1% claimed to practice one or more sports regularly (at least 4 hours/week for 9 months/year or more), 30.2% practice sports occasionally, and 40.7% no sports at all. The percentage of current smokers (at least one cigarette a month) increased from 9th grade (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
1
7
0
3
Order By: Relevance
“…This suggests that the consistent engagement in physical activity may reduce the likelihood of using cigarettes frequently or continuously, which has been documented in other countries previously [32, 33]. This is likely due to concerns regarding the capacity to engage in these activities if physical functioning is compromised or to social norms among peers being less supportive of smoking [32, 33]. Interestingly, research in other countries has also indicated that athletes often have higher smoking rates [54, 55].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This suggests that the consistent engagement in physical activity may reduce the likelihood of using cigarettes frequently or continuously, which has been documented in other countries previously [32, 33]. This is likely due to concerns regarding the capacity to engage in these activities if physical functioning is compromised or to social norms among peers being less supportive of smoking [32, 33]. Interestingly, research in other countries has also indicated that athletes often have higher smoking rates [54, 55].…”
Section: Discussionsupporting
confidence: 68%
“…In addition, low academic achievement [26, 31] and low school commitment or attachment [31] has been found to be risk factors for smoking among youth in developed countries. Additionally, engagement in sports or physical activity has been documented protective factors against smoking among youth [32, 33] as well as predictive of tobacco use [34, 35]. Finally, Internet use among youth has been a factor more recently examined and may indicate risk for exposure to tobacco advertising, as the Internet provides tobacco companies with a highly active environment to advertise their products in increasingly regulated countries [36, 37].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise might be expected to affect a person's attitude positively against smoking, within the concept of a healthier lifestyle. This attitude is also detected in a study of 1,462 students from Italy, where the correlation between exercise and smoking showed that whereas smoking incidence increases according to age, exercising persons present an opposite trend [14]. Also, the frequency of physical exercise is inversely associated with smoking [15].…”
Section: O P Y R Ig H T G E N E R a L P R A C T Ic E A Ir W A Y S Gmentioning
confidence: 67%
“…[2][3][4][5][6] There are also associations between patterns of physical activity and type of school, 7 8 school grades especially physical education, 9 and participation in organised sport. 8 9 In a Danish study, high school students participated more in leisure time sport and reached higher physical performance than students from technical or vocational schools, 7 but according to Telama et al 10 differences in physical activity by type of school were not strong in Finland.…”
mentioning
confidence: 99%